"Us foreigners": intersectionality in a scientific organization. Issue 6 (17th August 2015) - Wells, Celeste C.; Gill, Rebecca; McDonald, James
Abstract : Purpose: – The purpose of this paper is to explore intersectionality as accomplished in interaction, and particularly national difference as a component of intersectionality. Design/methodology/approach: – The authors use ethnographic, shadowing methods to examine intersectionality in-depth and developed vignettes to illuminate the experience of intersectionality. Findings: – National difference mitigated the common assumption in scientific work that tenure and education are the most important markers of acceptance and collegiality. Moreover, national difference was a more prominent driving occupational discourse in scientific work than gender. Research limitations/implications: – The data were limited in scope, though the authors see this as a necessity for generating in-depth intersectional data. Implications question the prominence of gender and (domestic) race/gender as "the" driving discourses of difference in much scholarship and offer a new view into how organizing around identity happens. Specifically, the authors develop "intersectional pairs" to understand the paradoxes of intersectionality, and as comprising a larger, woven experience of "intersectional netting." Social implications: – This research draws critical attention to how assumptions regarding national difference shape workplace experiences, in an era of intensified global migration and immigration debates. Originality/value: – The study foregrounds the negotiation of national difference in US workplaces, and focusses on how organization around said difference happens interactively in communication.